The Securitization of Women’s Migration and Access to Justice as Institutional Violence: Inter-American Standards and the Chilean Case - León Silva, Glorimar Alejandra (2026)
This article examines how the securitization of migration in Latin America—and particularly in Chile—reconfigures migration as a matter of public order, generating formal, material, and substantive barriers to migrant women’s access to justice and producing forms of institutional violence. In view of a fragmented literature on the scope of the right of access to justice and the absence of a systematic treatment of securitization with a gendered and intersectional focus, the study aims to demonstrate that this paradigm structurally undermines that right and that the Inter-American Human Rights System (IAHRS) offers sufficient normative and jurisprudential tools to counter it. Methodologically, it develops a qualitative analysis of doctrine, norms and Inter-American jurisprudence, with a case study of the Chilean regime (Law 21,325 and its regulation), incorporating an intersectional approach and an intercultural lens. The results show: a) that securitization replaces judicial review with expedited, standardized administrative procedures, eroding due process; b) that linguistic, economic and cultural barriers, together with fear of migratory consequences, inhibit reporting and litigation; c) that Chilean judicial practice is case-specific and asymmetrical in the application of conventionality control; and d) that the IAHRS sets operational standards—effective judicial protection, equality and non-discrimination, reinforced due diligence and normative adaptation—capable of reinstating limits on the State’s punitive power. It concludes that guaranteeing access to justice requires strengthening effective judicial review of detentions and expulsions, ensuring counsel and interpreters from the first procedural act, separating protection and enforcement channels, enshrining alternatives to detention in law and integrating intersectional analysis matrices into the reasoning of decisions. The principal contribution lies in articulating an operational framework to align migration policies with Inter-American standards, offering theoretical-practical inputs for administrative and judicial decision-making, and also for future agendas for empirical research.